Validitas Buku Ilmiah Populer Etnobotani Artocarpus altilis (Sukun) di Desa Sabuhur Kecamatan Jorong - Rina Rahmawati; Dharmono Dharmono; Mahrudin Mahrudin (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
Popular Scientific Book is one of learning resources that can be developed in teaching Ethnobotany. Ethnobotany is related to the use of plants by the local community. Information on ethnobotanical studies in the form of teaching materials is still limited. The use of regional potential-based teaching materials can be a source of learning and preservation of living things. It is necessary to develop teaching materials based on local potential. Prior to use, the BIP needs to be validated to identify deficiencies. This study aims to describe the validity of the popular scientific book Ethnobotani Artocarpus altilis in Sabuhur Village, Jorong District. BIP products were evaluated by Tessmer's formative test. Formative evaluation is limited to self-evaluation and expert testing. The results of the validation of the BIP show that the category is very valid on the contextual aspect, content completeness, appearance, and language, as well as according to the rules for its preparation.